Professional Competence And Higher Education - Winter, Richard; Maisch, Maire (Taylor & Francis, 1996)
First published in 1996. Routledge is an imprint of Taylor & Francis, an informa company.
English
Keywords: Education; core; assessment; criteria; asset; programme; statements; model; social; external; examiners